Hepatitis C in pregnant American Indian and Alaska native women; 2003-2015. Issue 1 (1st January 2019) - Nolen, Leisha D.; O'Malley, John C.; Seeman, Sara S.; Bruden, Dana J. T.; Apostolou, Andria; McMahon, Brian J.; Bruce, Michael G.
ABSTRACT: Recent reports have found a rise in Hepatitis C virus (HCV) infection in reproductive age women in the USA. Surveillance data suggests one group that is at increased risk of HCV infection is the American Indian and Alaska Native population (AI/AN). Using the National Center for Health Statistics (NCHS) birth certificate and the Indian Health Services, Tribal, and Urban Indian (IHS) databases, we evaluated reported cases of HCV infection in pregnant women between 2003 and 2015. In the NCHS database, 38 regions consistently reported HCV infection. The percentage of mothers who were known to have HCV infection increased between 2011 and 2015 in both the AI/AN population (0.57% to 1.19%, p < 0.001) and the non-AI/AN population (0.21% to 0.36%, p < 0.001). The IHS database confirmed these results. Individuals with hepatitis B infection or intravenous drug use (IDU) had significantly higher odds of HCV infection (OR 16.4 and 17.6, respectively). In total, 62% of HCV-positive women did not have IDU recorded. This study demonstrates a significant increase in the proportion of pregnant women infected with HCV between 2003 and 2015. This increase was greater in AI/AN women than non-AI/AN women. This highlights the need for HCV screening and prevention in pregnant AI/AN women.